Cleavage of fibrinogen by the human neutrophil neutral peptide-generating protease. - Wintroub, B U (1980)
The human neutrophil peptide-generating protease, which generates a low molecular weight vasoactive peptide from a plasma protein substrate, is directly fibrinolytic and cleaves human fibrinogen in a manner distinct from plasmin. Fibrinogen was reduced from 340,000 Mr to derivatives of 270,000-325,000 Mr during interaction with the protease at enzyme-to-substrate ratios of 0.3 or 1.0 microgram/1.0 mg. The 310,000-325,000 Mr cleavage fragments exhibited prolonged thrombin-induced clotting activity but were able to be coagulated, whereas the 270,000-290,000 Mr fragments were not able to be coagulated. Anticoagulants were not generated at either enzyme dose. As analyzed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis in 4-30% gradient gels and 10% gels stained for protein and carbohydrate, the diminution to 310,000-325,000 Mr and the prolongation of thrombin-induced clotting time resulted from cleavage of the fibrinogen A alpha chain. The further decrease in size to 270,000-290,000 Mr was associated with B beta-chain and gamma-chain cleavage and an inability to form gamma-gamma dimers. The neutral peptide-generating protease, a distinct human neutrophil neutral protease with fibrinolytic and fibrinogenolytic activities comparable to those of plasmin on a weight basis, cleaves fibrinogen in a manner that is distinct from the action of plasmin, leukocyte elastase, and leukocyte granule extracts. It may be that the concerted action of this neutrophil protease to generate a vasoactive peptide and to digest fibrinogen and fibrin facilitates neutrophil movement through vascular and extravascular sites.